EVALUASIPROGRAM NASIONAL PEMBERDAYAANMASYARAKAT MANDIRI PERKOTAAN DALAM PEMBANGUNAN KELURAHAN PAUDEAN KECAMATAN LEMBEH SELATAN KOTA BITUNG - Yohanis Maliogha; Charles R. Ngangi; Caroline B.D. Pakasi; Melissa L.G. Tarore (COCOS, 2015)
ABSTRACT  Yohanis Maliogha.Evaluation ofthe NationalProgramfor Community Empowermentin UrbanDevelopment of PaudeanVillage,SouthLembeh District,Bitung, under the guidance of Dr. Ir. Charles R. Ngangi, MSas the chair person, Dr.Ir. Caroline B. D. Pakasi, SP., MSi, Melissa Tarore, SP., MSi as members.  This study aims to evaluate the implementation of the program Urban PNPM development in the Paudean Village,South Lembeh Bitung District, basedon Context, Input, Process and Product. The method used in this research is purposive sampling method.  Data collection has been done for 3months since February toApril2015.The data used inthis studyare primary data and secondary data. Primary data were obtained using a list of questions to respondents. Secondary data were obtained fromt he board PNPM Urban and agencies associated with this research,which is Paudean village office.  The results showed that the evaluation of the implementation of development activities rebate road, drainage and revolving fund are running according with thep lanof development that wouldimpact on boththe environmentandsociety. But on the other hand the attention and supervision of government, community and program executorneed to be considered.  Keywords: Urban PNPM and Evaluation